(untitled) (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
Learning and understanding the science of recitation is very important because the law of reading the Qur’an with tajwid is fardhu ’ain, especially for future students of tahfidz candidates, especially in the implementation of learning at TPQ. In fact, there are often problems with learning tajwid at TPQ, especially in the village of Bedah Lawak, because the learning method is less attractive to students. As an effort to overcome this, the implementation of community service is carried out by empowering the way of teaching tajwid science at TPQ by using the mind mapping method. Based on the results of the implementation of community service by assessing the results of the application of mind mapping to students at TPQ, the score above the average score was 51.9 in the category of very good student response. This shows that the socialization of tajwid science using mind mapping learning media is well received. The dissemination of the science of recitation using mind-mapping learning media can provide a new understanding of TPQ youth, especially TPQ in Bedahlawak Village.